2015
DOI: 10.1038/srep14566
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell Derived Neuronal Cells Cultured on Chemically-Defined Hydrogels for Sensitive In Vitro Detection of Botulinum Neurotoxin

Abstract: Botulinum neurotoxin (BoNT) detection provides a useful model for validating cell-based neurotoxicity screening approaches, as sensitivity is dependent on functionally competent neurons and clear quantitative endpoints are available for correlating results to approved animal testing protocols. Here, human induced pluripotent stem cell (iPSC)-derived neuronal cells were cultured on chemically-defined poly(ethylene glycol) (PEG) hydrogels formed by “thiol-ene” photopolymerization and tested as a cell-based neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…However, the use of heterogeneous Matrigel with under-defined and complex protein components, may cause variability for drug testing [70, 97]. Natural hydrogels based on simple extracellular matrix protein components may be potential alternatives for Matrigel [76, 98, 99]. Synthetic hydrogels generally provide much better matrix uniformity and reproducibility than natural hydrogels [94, 100102].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…However, the use of heterogeneous Matrigel with under-defined and complex protein components, may cause variability for drug testing [70, 97]. Natural hydrogels based on simple extracellular matrix protein components may be potential alternatives for Matrigel [76, 98, 99]. Synthetic hydrogels generally provide much better matrix uniformity and reproducibility than natural hydrogels [94, 100102].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…While previous data has indicated greater sensitivity of iCell Neurons compared to HIP Neurons (Pellett, et al, 2015; Whitemarsh, et al, 2013), the HIP Neurons can be seeded at greater density resulting in higher total protein concentration in cell lysates. The protein concentrations of the cell lysates were determined to be 90.4 ±12.2 and 285 ± 36.7 μg / ml for iCell Neurons and HIP Neurons, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Jones, personal communication) can be used to detect intracellularly cleaved SNAP-25 in a sensitive hiPSC derived neurons cell model (Pellett, et al, 2015; Whitemarsh, et al, 2012), detection of cleaved SNAP-25 in cell lysates from hiPSC derived neurons exposed to serial dilutions of BoNT/A1was compared by ELISA and Western blot. While the Western blot data indicated dose-dependent SNAP-25 cleavage ranging from 100 % to 0 % cleavage as previously described (Whitemarsh, et al, 2012), the ELISA resulted in a very low and non-quantifiable signal (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations